Biogas production, DOM performance and microbial community changes in anaerobic co-digestion of chicken manure with Enteromorpha and green waste. (March 2022) - Zhao, Shunan; Chen, Wenhan; Liu, Manli; Lv, Huanyu; Liu, Yunguo; Niu, Qigui
Abstract: With the invasion of green tides and the increase of worldwide urban green areas, millions of tons of Enteromorpha (EN) and green waste (GW) needed to be reutilized. In mono-digestion, the low hydrolysis rate of Enteromorpha and green waste limited the biomethane production. In this study, chicken manure (CM), as co-substance, was added into EN and GW digestion systems to improve the biomethane production. The maximum biomethane production rate exhibited 49.9% improvement in co-digestion (CM:GW = 1:3). Besides, the heterogeneity of EN and GW induced PARAFAC components variation. The location of humic-like substance and tryptophan-like substance has significantly changed in excitation–emission matrix (EEM) spectra. Moreover, co-digestion significantly enhanced the cellulase activity in EN and GW co-digestion with 234% and 30% enhancement, respectively. Furthermore, the microbial community analysis indicated that co-digestion enriched the hydrogenotrophic methanogens ( Methanobacterium ). The potential metabolic pathway analysis showed an increasing trend in the methanogenesis encoding enzyme abundance. Graphical abstract: Image 1 Highlights: Co-digestion significantly improved the cellulase activity by 234% with GW. Hydrogenotrophic Methanobacterium increased from 12.0% to 43.7% in co-digestion. The maximum biomethane production rate enhanced 49.9% in co-digestion. Co-digestion could counter endogenous salinity press of Enteromorpha. The heterogeneity of substance induced PARAFAC components changes.